Genetic engineering of cytokinin metabolism: prospective way to improve agricultural traits of crop plants - Zalabák, David; Pospíšilová, Hana; Šmehilová, Mária; Mrízová, Katarína; Frébort, Ivo; Galuszka, Petr (Biotechnology advances, 2013)
Cytokinins (CKs) are ubiquitous phytohormones that participate in development, morphogenesis and many physiological processes throughout plant kingdom. In higher plants, mutants and transgenic cells and tissues with altered activity of CK metabolic enzymes or perception machinery, have highlighted their crucial involvement in different agriculturally important traits, such as productivity, increased tolerance to various stresses and overall plant morphology. Furthermore, recent precise metabolomic analyses have elucidated the specific occurrence and distinct functions of different CK types in various plant species. Thus, smooth manipulation of active CK levels in a spatial and temporal way could be a very potent tool for plant biotechnology in the future. This review summarises recent advances in cytokinin research ranging from transgenic alteration of CK biosynthetic, degradation and glucosylation activities and CK perception to detailed elucidation of molecular processes, in which CKs work as a trigger in model plants. The first attempts to improve the quality of crop plants, focused on cereals are discussed, together with proposed mechanism of action of the responses involved.
Keywords: Crops, Agricultural; Oxidoreductases; signální transdukce; genetické inženýrství; zemědělské plodiny; proteinkinasy; Plant Proteins; oxidoreduktasy; histidinkinasa; Cytokinins; Signal Transduction; Stress, Physiological; cytokininy; Plants, Genetically Modified; Protein Kinases; geneticky modifikované rostliny; Alkyl and Aryl Transferases; glykosylace; fyziologický stres; Glycosylation; Genetic Engineering; alkyltransferasy a aryltransferasy; rostlinné proteiny; Histidine Kinase